Regulating of Passages in the Motorway Central Reserve - Hozjan, Dubravka; Blašković-Zavada, Jasna; Novačko, Luka (Promet - Traffic&Transportation, 2007)
Passages in the central resetVes of mot01ways are intendedfor redirection of traffic during planned special maintenance ofmotorways and in accident situations, as well as for the requirementsof emergency vehicles (ambulance, fire-brigade, police).The observed problems in deficient legal regulations of thedesign and length of the passages are reflected on the existingcondition of the passages in the central resetVe on the Croatianmotorways. Our practice shows diverse solutions, especially regardingthe lengths of the passages.Considering the issue of the passages in the motorway centralresetVes in a certain number of the European Union countriesone can notice various design solutions contained in thenational standards. Having in mind the purpose of the passagesunder the condition of safe flow of traffic, the required passagedimensions have been studied regarding their position on themotorway. The study resulted in two design type solutions.As result of the perfonned study and the obsetVation of thenational and foreign practice, recommendations are given forthe design solution of the passage in the central rese1ve on theCroatian motorways.